Regime shifts shorten food chains for mesopredators with potential sublethal effects. (15th January 2018) - Hempson, Tessa N.; Graham, Nicholas A. J.; MacNeil, M. Aaron; Bodin, Nathalie; Wilson, Shaun K.
Abstract: Predator populations are in decline globally. Exploitation, as well as habitat degradation and associated changes in prey availability are key drivers of this process of trophic downgrading. In the short term, longevity and dietary adaptability of large‐bodied consumers can mask potential sublethal effects of a changing prey base, producing a delayed effect that may be difficult to detect. In coral reef ecosystems, regime shifts from coral‐ to algae‐dominated states caused by coral bleaching significantly alter the assemblage of small‐bodied reef fish associated with a reef. The effects of this changing prey community on reef‐associated mesopredators remains poorly understood. This study found that the total diversity, abundance and biomass of piscivorous mesopredators was lower on regime‐shifted reefs than recovering reefs, 16 years after the 1998 mass coral bleaching event. We used stable isotope analyses to test for habitat‐driven changes in the trophic niche occupied by a key piscivorous fishery target species on reefs that had regime‐shifted or recovered following climatic disturbance. Using morphometric indices, histology, and lipid analyses, we also investigated whether there were sublethal costs for fish on regime‐shifted reefs. Stable isotopes demonstrated that fish from regime‐shifted reefs fed further down the food chain, compared to recovering reefs. Lower densities of hepatocyte vacuoles in fish from regime‐shifted reefs, and reduced lipid concentrations in spawning females from these reefs, indicated a reduction in energy stores, constituting a sublethal and potential delayed effect on populations. Reduced energy reserves in mesopredators could lead to energy allocation trade‐offs, and decreased growth rates, fecundity and survivorship, resulting in potential population declines in the longer term. A plain language summary is available for this article. Abstract : Plain Language Summary